Integration of Environmental Literacy in IPAS Learning to Enhance the Ecological Awareness of Fifth Grade Students at MI Darul Ulum 02 Kudus - Azizah, Wafiq; Putri, Laisya Syifana Hariyanto; Ahsani, Eva Luthfi Fakhru (Sekolah Tinggi Agama Islam Syekh Abdur Rauf Aceh Singkil, Aceh, Indonesia, 2025)
The low awareness of environmental literacy has led many individuals to perceive environmental issues as trivial. In fact, environmental literacy plays a crucial role in human survival, particularly in fostering responsible ecological awareness. Therefore, implementing environmental literacy from an early age is an urgent necessity to ensure that students develop a strong understanding of the importance of maintaining environmental balance. This study aims to analyze the integration of environmental literacy in IPAS (Natural and Social Sciences) learning to enhance the ecological awareness of fifth-grade students at MI Darul Ulum 02 Kudus. The research method used is a quantitative approach. The results of this classroom action research indicate that integrating environmental literacy into IPAS learning can improve students' ecological awareness, as evidenced by positive outcomes. The percentage of students achieving different levels of success is as follows: 53.33% of students received an excellent rating, 26.67% received a good rating, and only 20% received a sufficient rating. These percentages demonstrate that conducting classroom action research in two cycles has had a positive impact on improving students' understanding of environmental literacy and their ecological awareness in the fifth grade of MI Darul Ulum 02 Kudus. [Kesadaran yang rendah terhadap literasi lingkungan menyebabkan banyak individu menganggap isu lingkungan sebagai hal yang sepele. Padahal, literasi lingkungan memiliki peran krusial dalam kelangsungan hidup manusia, terutama dalam menumbuhkan kesadaran ekologis yang bertanggung jawab. Oleh karena itu, penerapan literasi lingkungan sejak dini menjadi kebutuhan mendesak untuk memastikan bahwa siswa memiliki pemahaman yang kuat tentang pentingnya menjaga keseimbangan lingkungan. Penelitian ini bertujuan untuk menganalisis integrasi literasi lingkungan dalam pembelajaran IPAS (Ilmu Pengetahuan Alam dan Sosial) guna meningkatkan kesadaran ekologis siswa kelas V di MI Darul Ulum 02 Kudus. Metode penelitian yang digunakan adalah pendekatan kuantitatif. Hasil penelitian tindakan kelas ini menunjukkan bahwa integrasi literasi lingkungan dalam pembelajaran IPAS dapat meningkatkan kesadaran ekologis siswa, sebagaimana dibuktikan oleh hasil yang positif. Persentase siswa yang mencapai berbagai tingkat keberhasilan adalah sebagai berikut: 53,33% siswa memperoleh predikat sangat baik, 26,67% memperoleh predikat baik, dan hanya 20% yang memperoleh predikat cukup. Persentase ini menunjukkan bahwa pelaksanaan penelitian tindakan kelas dalam dua siklus telah memberikan dampak positif terhadap peningkatan pemahaman siswa mengenai literasi lingkungan serta kesadaran ekologis mereka di kelas V MI Darul Ulum 02 Kudus].